Pacientes em processo diagnóstico de câncer de cabeça e pescoço: aspectos psicológicos, percepções e expectativas - Graner, Karen Mendes [UNESP] (2013)
This study aimed to describe the sociodemographic characteristics, lifestyle, and physical and mental health status of patients with head and neck cancer, as well as identify their perceptions and expectations regarding care and diagnosis. 49 patients were evaluated before and after diagnosis communication as they were submitted to biopsies in two diagnostic oral centers. Before the diagnosis (moment 1), the sociodemographic and lifestyle variables were evaluated using a questionnaire and validated instruments to assess anxiety (State - Trait Anxiety Inventory, STAI), depression (Beck Depression Inventory, BDI) and alcohol abuse (Alcohol Use Disorders Identification Test, AUDIT); reason for examination, feelings, perception of the problem, and expectations were investigated through a structured interview. After cancer diagnosis (moment 2), 29 patients had some aspects reassessed: anxiety, depression levels, perceptions, feelings about the disease, and expectations towards medical and dental care. Were also investigated coping and satisfaction with the service received from dentists. Data collected during the interviews were categorized and a descriptive and bivariate analysis (Qui-square, fisher, Goodman and Wilcoson – p<0,05) to other variables. The initial sample consisted mostly of males (73.4%) (mean age of 59 years), with four and a half years of study, employed (40.8%), low income (53,0%), having a partner (61.2%), living with relatives (87.8%), having feelings of social support (83.7%) and a religion (93.9%), smoking (44.9%) and (45.0%) drinking habits, and classified their health as “good” (69.4%). The mean time between observation of symptoms and seeking for help was six months, which were mostly intraoral lesions (83.7%), referred by dentists (51.1%). Before diagnosis (Moment 1), women had a high prevalence for anxiety-trait (53.9%), state (61.5%) and depressive symptoms (46.2%). Men had a higher frequency of risky use of ...